Asymmetric modeling of the fiscal policy–economic growth nexus in Somalia - Abdullahi Osman Ali; Jama Mohamed; Mohamed Osman Mohamed (Cogent Economics & Finance, 2024)
Somalia has faced a prolonged challenge of high dollarization, which has limited the effectiveness of conventional monetary policy tools. In response, fiscal policy has taken center stage as the primary means of economic management by the government. This study aims to investigate the asymmetric impact of fiscal policy on Somalia's economic growth, utilizing annual time series data spanning from 1970 to 2019 and employing the Nonlinear Autoregressive Distributed Lag (NARDL) model. The results indicated the existence of cointegration among the variables. In the long run, both increases and decreases in government expenditure exhibited a significant positive effect on economic growth, with a more pronounced impact observed for decreases in public expenditure compared to increases in government spending. Furthermore, in the short run, both increases and decreases in government expenditure had a significant positive effect on economic growth, although an increase in government spending showed a stronger impact on economic growth compared to a decrease in government expenditure. Notably, the study surpassed various diagnostic tests, ensuring the robustness of the findings. Based on these results, we recommend that policymakers prioritize fiscal policy, particularly public spending, as a crucial channel for fostering economic growth. Additionally, directing public spending towards productive sectors of the economy and promoting fiscal transparency are suggested as means to achieve fiscal policy objectives effectively. Somalia faces a persistent challenge of high dollarization, rendering conventional monetary policy tools ineffective. In response, fiscal policy has become the primary tool for economic management. The asymmetric impact of fiscal policy on economic growth in Somalia remains an underexplored area in the literature, particularly in the context of a least developed country. The research takes the initiative to investigate and understand the asymmetric impact of fiscal policy on Somalia's economic growth. By utilizing the NARDL model, it aims to provide policymakers with nuanced insights into the specific dynamics of fiscal policy in Somalia. The study evaluates both expansionary and contractionary fiscal policies to offer comprehensive recommendations for effective economic development in this unique and complex environment. Policymakers in Somalia benefit from tailored strategies derived from the study, enabling them to navigate the economic challenges effectively. Researchers and economists gain valuable insights into the asymmetric effects of fiscal policy in a least developed country, contributing to the broader understanding of economic dynamics. The government of Somalia can use the research findings to enhance the design and implementation of fiscal policies, particularly in the allocation of public spending, fostering more effective economic growth. The general population in Somalia stands to benefit from improved economic conditions resulting from more targeted and efficient fiscal policies. This may lead to increased employment opportunities and better living standards. The research contributes to the broader scientific understanding of fiscal policy dynamics in least developed countries. This understanding is crucial for the global community in shaping policies that address the unique challenges faced by such nations. Scholars and researchers focused on economic development, especially in least developed countries, gain from the study's methodology and findings. It adds a nuanced perspective to the existing literature on fiscal policy impacts.
Keywords: 330; Fiscal policy; NARDL; economic growth; asymmetric effect